2013
DOI: 10.1111/wre.12045
|View full text |Cite
|
Sign up to set email alerts
|

Impact of site conditions and farming practices on the occurrence of rare and endangered weeds on arable land in the Czech Republic

Abstract: This article documents the impact of site conditions and farming practices on the occurrence of rare and endangered weeds on arable land in the Czech Republic. A survey was conducted between 2006 and 2008 in winter cereals, spring cereals and wide-row crops. The relationship between the occurrence of plants and explanatory factors was analysed using a multivariate analysis to calculate species frequencies in different types of farming, crops and altitudes. In total, 290 relev es were recorded, with a total num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 18 publications
1
20
0
2
Order By: Relevance
“…; Kolárová et al. ) is generally attributed to a lack of herbicide application and reduced amounts of fertilizer (Cirujeda et al. ; Rassam et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Kolárová et al. ) is generally attributed to a lack of herbicide application and reduced amounts of fertilizer (Cirujeda et al. ; Rassam et al.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany and Austria, Callauch (1981), Plakolm (1989), van Elsen (1989, Wolff-Straub (1989) and Frieben et al (2012) compared numbers of endangered species in organic and conventional fields, all finding higher numbers of such species in organic systems. In a survey based on 290 relevés in the Czech Republic, the sum of frequencies of endangered arable species in organically managed fields was 4.5 times higher than in conventional farming (Kolářová, Tyšer, and Soukup 2013b). In the Mediterranean, in Catalonia, Rotchés-Ribalta et al (2015a) found a whole range of threatened non-crop species in organically managed fields.…”
Section: Conservation Strategies At the Farm Scalementioning
confidence: 99%
“…The link between flora species richness and the nature conservation value of field habitats is generally based on the assumption that there should be a higher proportion of rare flora species if total flora species richness increases (Kolářová et al, 2013). This in turn, should have a positive impact on compliance with the criteria rareness/endangerment (vulnerability) and naturalness.…”
Section: Conceptual Modelmentioning
confidence: 99%